Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Menjadi Nasabah Pada Bank Syariah Di Surabaya - Agus Sarwo Edi; Erwan Aristyanto (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to know and describe the analysis of factors that affect people's interest in becoming customers in sharia bank. Respondents to the analysis in this study were residents in Surabaya City as many as 100 people.Samples are taken using incidental sampling techniques that use samples based on accidentally meeting with researchers when viewed by a suitable person as a data source. Data analysis is performed using statistics with SPSS version 20 tools. Based on the results of data analysis using t test it is known that partially partial knowledge variables have a positive and significant effect on public interest.Location variables have no positive and insignificant effect on public interest.Promotion variables have a positive and significant effect on people's interests. Simultaneous results of knowledge, location, and promotion have a significant effect on people's interest in becoming customers in Sharia banks.There is a dominant influence on people's interest in becoming customers in sharia banks indicated by promotional variables.